2021
DOI: 10.1111/acv.12734
|View full text |Cite
|
Sign up to set email alerts
|

Capture‐induced vulnerability in male Shortnose guitarfish during their reproductive period

Abstract: The assessment of physiological responses to capture provides useful information for elasmobranch conservation. In particular, understanding these impacts in species caught as bycatch that are released after capture can predict their "post-release" fate and aid in management plans. Although well studied in several species, capture-stress is nonetheless frequently assessed without considering putative variability between sexes. Given the high mortality of pregnant Zapteryx brevirostris females reported in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Release can be an effective and low-cost conservation measure in tropical, mixed species fisheries, especially when measures like spatial closures or gear modifications are not feasible (Gupta et al, 2020;Wosnick et al, 2022). Although poorly studied, some studies have noted moderate to high survival rates post-capture for different rhino ray species (Fennessy, 1994;Prado et al, 2021;Stobutzki et al, 2002); high survival has also been observed by fishers in our study site.…”
Section: Live Release Measures For Rhino Raysmentioning
confidence: 60%
“…Release can be an effective and low-cost conservation measure in tropical, mixed species fisheries, especially when measures like spatial closures or gear modifications are not feasible (Gupta et al, 2020;Wosnick et al, 2022). Although poorly studied, some studies have noted moderate to high survival rates post-capture for different rhino ray species (Fennessy, 1994;Prado et al, 2021;Stobutzki et al, 2002); high survival has also been observed by fishers in our study site.…”
Section: Live Release Measures For Rhino Raysmentioning
confidence: 60%
“…Identifying the reproductive seasonality of threatened elasmobranchs is crucial, especially due to their high vulnerability to anthropogenic impacts during this period, e.g ., increased catch in commercial fisheries during reproductive aggregations ( e.g ., Bada‐Sánchez et al ., 2019), higher incidence of abortion ( e.g ., Adams et al ., 2018) and pronounced responses to fishing‐induced stress and higher mortality rates ( e.g ., Prado et al ., 2022). Thus, the objective of this study was to examine the occurrence of mating wounds and scars in female Caribbean reef sharks at the Fernando de Noronha Archipelago, a region previously described as a nursery area for this species (Garla et al ., 2006a, 2006b).…”
Section: Figurementioning
confidence: 99%
“…In fact, the reproductive period is very costly for sharks and rays, as part of the dietary intake is directed to gamete production and offspring maintenance. In viviparous species, the cost of reproduction is so elevated that studies indicate higher parental mortality upon capture stress during the copulation (males) and embryonic development (females) phases, due to the inability of individuals to properly direct stored energy to deal with allostatic overload and recover both homeostatic and acid-basic balances ( Wosnick et al, 2019 ; Prado et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%